Brittle bone brothers: osteogenesis imperfecta conventional serial case - Marsha Ruthy Darmawan; Elysanti Dwi Martadiani (DiscoverSys Inc., 2021)
Background: Osteogenesis Imperfecta (OI) is a heredity connective tissue disorder due to COL1A1/2 gene mutation, causing a defect in encoding proteins to metabolize collagen. One of OI’s manifestations to musculoskeletal is bone incompetence, hence the name Brittle bone disease. We report three cases of OI type IV in adults with pathognomonic radiology findings.Case Presentation: In Case 1, a 40-year-old Indonesian male came to the hospital with small stature and unsuited with his age. Conventional radiology examination found OI on all four extremities, anterior dislocation of left shoulder, and old fracture with an acute angle in the left radial shaft. In Case 2, a 41-year-old Indonesian male came to the hospital with short stature, causing limitation to his activities, and he confessed always to be shorter than people his age. Radiology evaluation suggests an OI in bilateral superior and inferior extremities, old fractures in the right humeral shaft also the left clavicle, acute angles right radius-ulna shaft, and osteoporosis in all visualized bones. In addition, in Case 3, a 42-year-old Indonesian male came to the hospital with short stature and pain within his bones, causing limitation to his activity. Conventional radiology imaging shows bilateral superior and inferior extremities, old fracture in the medial third of the left humerus and bilateral femur, acute-angled bilateral antebrachial-femur-cruris, and osteoporosisConclusion: Based on OI categorization, only type I and IV can live to adulthood, and the same type of OI can be found in siblings. Conventional radiology imaging provides a great help in diagnosing OI.